2013
DOI: 10.1080/07421656.2014.847049
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Art Therapy on Cognitive Performance Among Ethnically Diverse Older Adults

Abstract: The population of ethnically diverse older adults in the US is rapidly growing, and reports of cognitive impairments, such as those caused by Alzheimer"s disease, are becoming more prevalent. This investigation explored whether art therapy could provide cognitive benefits among an ethnically diverse (N = 133), particularly Latino/Hispanic, population of older adults who are often excluded from research on aging and cognition. Within the study, five art therapists, each in distinct cities throughout three US st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 157 publications
(283 reference statements)
0
19
1
1
Order By: Relevance
“…The result on cognitive measure indicated that 12 sessions of social art activities is not enough to improve cognitive functioning. This result is different from earlier research (see Pike, 2013).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The result on cognitive measure indicated that 12 sessions of social art activities is not enough to improve cognitive functioning. This result is different from earlier research (see Pike, 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…Depressive symptoms in later life have had low priority in clinical research of psychotherapeutic treatment (Munk, 2007), yet they contribute to a deterioration of physical and functional health (Choi, Ransom & Wyllie, 2008), and are prevalent in nursing homes (Meeks, et.al, 2015). Depression in nursing home residents has been found to be related to decrease in cognitive functions and to result in an increased burden for both residents and staff attempting to provide care (Cody & Drysdale, 2013;Pike, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This literature documented the use of expressive forms of drawing and painting. Several authors also mentioned the use of collage (Alders Pike, 2013;Carroll & Ribas, 2008;Landgarten, 1981;Liebmann, 2004;Riley, 1994Riley, , 1999Woolhiser Stallings, 2010). Due to the techniques employed, all of the lifelines, and their variations, in the above-referenced examples would have been created in two dimensions.…”
Section: Review Of the Literaturementioning
confidence: 93%
“…They have been used with adults (Brown, 1970;Fausek, 1997;Fitzpatrick, 2002;Ford, 1990;Frings Keyes, 1983;Gladding, 1998Gladding, , 2012Hass-Cohen, 2008a;Hoshino & Cameron, 2008;Landgarten, 1981;Liebmann, 2004Liebmann, , 2012Martin, 1997Martin, , 2003MeijerDegen, 2006;Miller, 1993;Rappaport, 2009;Rhyne, 1973;Ricco, 2007;Robbins, 1994;Ross, 1997;Rubin, 2005aRubin, , 2010Silverstone, 1991;Thornton, 1990;Tracz & Gehart-Brooks, 1999;van der Velden & Koops, 2005). Also, older adults have benefited from their use (Alders Pike, 2013;Bergland, 1982;Martin, 2003;Ravid-Horesh, 2004;Woolhiser Stallings, 2010). This literature documented the use of expressive forms of drawing and painting.…”
Section: Review Of the Literaturementioning
confidence: 98%
“…For example, Antoniou et al [2] proposed using foreign language learning programs aimed at older populations for building cognitive reserve as language learning engages an extensive brain network that is known to overlap with the regions negatively affected by the aging process. Pike [10] suggested art therapy treatment to improve cognitive performance of elderly people.…”
Section: Related Workmentioning
confidence: 99%